Quo vaditis litterae postmodernae? Is postmodernism the end of literature? - Soukup, Jan (Romanica Olomucensia, 2025)
This study examines a cardinal question in recent debates: whether postmodernism can be understood as the end of literature or, on the other hand, as a new era of liberation, the era that celebrates the emancipatory potential of postmodern play with language and intertextuality. In order to illustrate two opposing poles, this research is based on philosophers and literary critics who seem to be able to bring some clarity to the discussion that forms the core of this study. Among the critics who adopt a suspicious attitude towards postmodernism are Michel Maffesoli, Anna Hogenová, and Rosalind Krauss. On the other side of the barricade are Linda Hutcheon, Julia Kristeva, and Umberto Eco. After the two opposing positions are analysed, the concrete manifestations of this duality are identified. Sceptics understand postmodernism as a form of decline associated with the predominance of market and performance criteria in the production and reception of literary works. Proponents of postmodernism characterise it as the era of subjectivity, of experimentation favouring artistic freedom at the expense of previously accepted rules, concepts, and even value systems. Although the answer to the question posed at the beginning does not seem to have a definitive solution, this study proposes a clear distinction between two conceptions of postmodernism and attempts to present a certain panorama of contemporary debates on postmodern literature.
Keywords: end of literature; postmodernism; late capitalism; decline; deconstruction; metatextuality